Consumer behaviour in China : customer satisfaction and cultural values - Yau, Oliver H. M. (Oliver Hon-Ming), 1946- (London : Routledge, 1994)
This book is about: Comsumer satisfaction and dissatisfaction; A structural model of Chinese cultural values and consumer satisfaction/dissatisfaction...
Keywords: Consumer behavior; Consumer behavior -- China; Consumer satisfaction -- China